Barriers to Initiating and Continuing Mental Health Treatment Among Soldiers in the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS). Issue 9 (1st September 2016) - Naifeh, James A.; Colpe, Lisa J.; Aliaga, Pablo A.; Sampson, Nancy A.; Heeringa, Steven G.; Stein, Murray B.; Ursano, Robert J.; Fullerton, Carol S.; Nock, Matthew K.; Schoenbaum, Michael; Zaslavsky, Alan M.; Kessler, Ronald C.
ABSTRACT: U.S. Army soldiers with mental disorders report a variety of barriers to initiating and continuing treatment. Improved understanding of these barriers can help direct mental health services to soldiers in need. A representative sample of 5, 428 nondeployed Regular Army soldiers participating in the Army Study to Assess Risk and Resilience in Servicemembers completed a self-administered questionnaire and consented to linking self-administered questionnaire data with administrative records. We examined reported treatment barriers (perceived need, structural reasons, attitudinal reasons) among respondents with current Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, mental disorders who either did not seek treatment in the past year ( n = 744) or discontinued treatment ( n = 145). About 82.4% of soldiers who did not initiate treatment and 69.5% of those who discontinued treatment endorsed at least two barriers; 69.8% of never-treated soldiers reported no perceived need. Attitudinal reasons were cited more frequently than structural reasons among never-treated soldiers with perceived need (80.7% vs. 62.7%) and those who discontinued treatment (71.0% vs. 37.8%). Multivariate associations with sociodemographic, Army career, and mental health predictors varied across barrier categories. These findings suggest most soldiers with mental disorders do not believe they need treatment and those who do typically face multiple attitudinal and, to a lesser extent, structural barriers.